Subacute Stroke in a Young Female: A Case of Moyamoya Syndrome Initially Anchoring with Anxiety - Saira Chaughtai; Zeeshan Chaughtai; Muhammad Shaheryar Haider; Hasnan M. Ijaz; Sarah Elmedani; Mohamed Bakr; Mohammad A. Hossain; Arif Asif (Case Reports in Medicine)
Moyamoya disease is an arterial disorder causing stroke in a young patient. This is a chronic condition causing progressive cerebrovascular disease due to bilateral stenosis and occlusion of the arteries around the circle of Willis, with prominent arterial collateral circulation. It was first described in Japan and subsequently reported in other Asian countries, but infrequently found in the Western world. Interestingly, there may be racial differences in the presentation and subsequent prognostication of treatment of moyamoya. It is diagnosed with classic angiographic findings of stenosis or occlusion of the circle of Willis vessels. Here, we describe a 28-year-old Caucasian female who was initially diagnosed with anxiety when she presented with symptoms of impaired concentration and fatigue. After the development of remitting slurred speech and facial droop, magnetic resonance imaging and cerebral angiogram yielded the discovery of high-grade stenosis of the origin of the left middle cerebral artery with associated thrombosis in that area. She did well after getting surgery and rehabilitation. This demonstrates a unique presentation of prominent psychiatric symptoms initially thought to be anxiety and culminated in the finding of ischemic stroke in an adult patient with moyamoya.